A real-time passive acoustic monitoring system to detect Yangtze finless porpoise clicks in Ganjiang River, China - Li, Weilun; Qiu, Jiansong; Lei, Peiyu; Chen, Xiaohong; Fan, Fei; Deng, Xiaojun; Dai, Yingen; Deng, Yanqing; Wang, Kexiong; Mei, Zhigang (Frontiers in Marine Science, 2022)
Phocoenidae live in fresh, coastal waters where they often share a significant portion of their habitat with humans. As a result, local activities (e.g., coastal fisheries and shipments) cause underwater noise pollution and threaten their ecosystem. To better conserve the habitat of porpoises, we aimed to study their activities in these waters by recording their echolocation clicks using a passive acoustic monitoring (PAM) system. However, because the off-line PAM instruments were often used in the past that need to be periodically deployed and recovered, data acquisition is typically obtained and analyzed in batches, rather than in real-time. A real-time PAM detection system would help minimize the impact of underwater noise on approaching porpoises. Furthermore, issues of bad quality data–with gaps due to loss or damage of the off-line PAM instruments–could be avoided with a real-time detection system. Therefore, in this study, we developed the Real-time Porpoise Click Detector-II (RPCD-II), equipped with a digital hydrophone, main memory (2 TB storage), a central processing unit, and a wireless transmission module. We deployed the RPCD-II under a docked fishing vessel at the Ganjiang River in Yangzi Zhou Town Fisheries Village, Nanchang City (8–9 December 2021), where it recorded signals of Yangtze finless porpoise and produced a real-time report. To validate the results of RPCD-II, another underwater sound recorder, the SoundTrap 300HF (ST), was also set up (as a control device) under the docked fishing vessel. Both devices recorded consistent results of 9330 clicks, further demonstrating RPCD-II’s ability for the real-time detection of Yangtze finless porpoise in the field.